Team work and cytopathology molecular diagnosis of solid pancreatic lesions. Issue 6 (16th March 2017) - Fabbri, Carlo; Gibiino, Giulia; Fornelli, Adele; Cennamo, Vincenzo; Grifoni, Daniela; Visani, Michela; Acquaviva, Giorgia; Fassan, Matteo; Fiorino, Sirio; Giovanelli, Silvia; Bassi, Marco; Ghersi, Stefania; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is expected to become the second leading cause of cancer‐associated death in the next decade or so. It is widely accepted that tumorigenesis is linked to specific alterations in key genes and pancreatic neoplasms are some of the best characterized at the genomic level. Recent whole‐exome and whole‐genome sequencing analyses confirmed that PDAC is frequently characterized by mutations in a set of four genes among others: KRAS, TP53, CDKN2A / p16, and SMAD4 . Sequencing, for example, is the preferable technique available for detecting KRAS mutations, whereas in situ immunochemistry is the main approach for detecting TP53 gene alteration. Nevertheless, the diagnosis of PDAC is still a clinical challenge, involving adequate acquisition of endoscopic ultrasound (EUS)‐guided fine‐needle aspiration (FNA) and specific pathological assessment from tissue architecture to specific biomolecular tests. The aim of the present review is to provide a complete overview of the current knowledge of the biology of pancreatic cancer as detected by the latest biomolecular techniques and, moreover, to propose a paradigm for strict teamwork collaboration in order to improve the correct use of diagnostic sources.